2016
DOI: 10.1111/jac.12175
|View full text |Cite
|
Sign up to set email alerts
|

Role of Arbuscular Mycorrhiza in Alleviating Salinity Stress in Wheat (Triticum aestivum L.) Grown Under Ambient and Elevated CO2

Abstract: Plant growth and development are influenced by future elevated atmospheric CO 2 concentration and increased salinity stress. AM (arbuscular mycorrhiza) symbiosis has been shown to improve plant growth and resistance to environmental stresses. The aim of this study was to investigate the potential role of AM fungus in alleviating salinity stress in wheat (Triticum aestivum L.) plants grown under ambient and elevated CO 2 concentrations. Wheat plants inoculated or not inoculated with AM fungus were grown in two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 51 publications
(127 reference statements)
3
19
0
Order By: Relevance
“…However, shoot N concentration was lower in the AM plants than that in the non‐AM plants under elevated CO 2 and salt stress (Tab. ), which is consistent with the results of Zhu et al (). An extra increase in C accumulation and growth of the AM plants was observed in relation to N uptake, indicating an N dilution effect ( Zhu et al, ).…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…However, shoot N concentration was lower in the AM plants than that in the non‐AM plants under elevated CO 2 and salt stress (Tab. ), which is consistent with the results of Zhu et al (). An extra increase in C accumulation and growth of the AM plants was observed in relation to N uptake, indicating an N dilution effect ( Zhu et al, ).…”
Section: Discussionsupporting
confidence: 94%
“…Our previous study showed that salt stress inhibited AM colonization, while elevated CO 2 concentration enhanced AM colonization ( Zhu et al, ). Plants under elevated CO 2 might allocate more C to AM fungi and benefit the AM colonization ( Compant et al, ).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…It is known that AMF are largely dependent on their host plant for carbon, so they are sensitive to climatic changes that affect their host plant [ 14 ]. In this sense, eCO 2 could have an indirect effect on mycorrhizal colonization by promoting carbon assimilation and allocation to roots [ 29 ]. Since AMF are attached to plant roots, they are lucky to receive higher amount of photosynthates under eCO 2 before other soil microbes [ 30 ].…”
Section: Resultsmentioning
confidence: 99%